An optimizing model for solving outsourcing supplier selecting problem based on particle swarm algorithm. (17th November 2018) - Li, Yibing; Ding, Kang; Wang, Lei; Zheng, Wenkai; Peng, Zhao; Guo, Shunsheng
ABSTRACT: The characteristics of decentralization, diversification, and dynamics of outsourcing resources put forward higher requirements for the supplier selection in manufacturing enterprises. For building materials equipment manufacturing enterprises (BMEM), due to the complex product structure, the demand for outsourcing resources is very large. The traditional method is difficult to meet the needs of current outsourcer evaluation and selection. In order to solve the problem, this paper establishes an outsourcing supplier selection model based on the quality, price, delivery time, reliability, and availability of outsourced suppliers. And then, a hybrid supplier selection algorithm based on Analytic Hierarchy Process (AHP) and Particle Swarm Optimization (PSO) is designed in this paper. Finally, the model and algorithm are verified and analyzed in BMEM. The paper also compares the algorithm with genetic algorithm (GA) and ant colony optimization (ACO). The experimental results show that the model can effectively improve the effectiveness and reliability of outsourcing supplier selection.